JENIS KUSKUS (Phalangeridae) DI PULAU RATEWI NABIRE PAPUA - Freddy Pattiselanno; Deny A. Iyai (Jurnal Natural, 2009)
Cuscus exploration has been conducted in order to identify the presence of cuscus in Ratewi Island, around the coastal site of Napan Yaur, Nabire, Papua. The study was designed in descriptive method with case study. The results indicated that two cuscus species was found, they were Kuskus Coklat (Phalanger orientalis) and Kuskus Bertotol (Spilocuscus maculatus)